Formulation and cytotoxicity evaluation of new self-emulsifying multiple W/O/W nanoemulsions - Sigward E (Dove Medical Press, 2013)
Estelle Sigward,1 Nathalie Mignet,1 Patrice Rat,2 Mélody Dutot,2 Saleh Muhamed,1 Jean-Michel Guigner,3 Daniel Scherman,1 Denis Brossard,1 Sylvie Crauste-Manciet11Chemical, Genetic and Imaging Pharmacology Laboratory; INSERM U1022, CNRS UMR8151, Chimie ParisTech, Faculty of Pharmacy, Paris Descartes University, Sorbone Paris Cité, Paris, France; 2Chemistry-Cellular and Analytical Toxicology Laboratory (C-TAC), Faculty of Pharmacy, Paris Descartes University, Sorbone Paris Cité, Paris, France; 3Institut de Minéralogie et de Physique des Milieux Condensés IMPMC -IRD-CNRS UMR 7590, Université Paris Pierre et Marie Curie, Paris, FranceAbstract: Three multiple water-in-oil-in-water (W/O/W) nanoemulsions have been designed for potential inclusion of either lipophilic or hydrophilic drugs using a two-step emulsification process exclusively based on low-energy self-emulsification. The W/O primary emulsion was constituted by a blend of oil (medium chain triglyceride), a mixture (7:3) of two surfactants, and a 10% water phase. The surfactants were a mixture of Polysorbate-85/Labrasol®, Polysorbate-85/ Cremophor® EL or glycerol/Polysorbate-85. The final W/O/W nanoemulsions were obtained by the addition of water, with a weight ratio nanoemulsion/water of 1:2. The multiple emulsion stability was found to increase from 24 hours to 2 and 6 months with Labrasol, glycerol, and Cremophor, respectively. Cytotoxicity was found for formulations including Labrasol and Cremophor EL. The concentration of emulsion inhibiting 50% cell viability (IC50) was determined using the alamarBlue® test, giving after 24 hours of incubation, IC50 = 10.2 mg/mL for the Labrasol formulation and IC50 = 11.8 mg/mL for the Cremophor EL formulation. Corresponding calculated IC50 values for surfactants were 0.51 mg/mL for Labrasol and 0.59 mg/mL for Cremophor EL. In both cases, cytotoxicity was due to an apoptotic mechanism, evidenced by chromatin condensation and P2X7 cell death receptor activation. The formulation including glycerol, investigated between 1 and 100 mg/mL concentration of nanoemulsion, did not affect cell viability. Moreover, neither chromatin condensation nor P2X7 activation was found between the 10 and 30 mg/mL final concentration of the emulsion. This last formulation would therefore be of major interest for further developments.Keywords: Labrasol, Cremophor EL, apoptosis, P2X7 receptor, polysorbate, glycerol